Curriculum standards and textbook coverage of fractions in high-achieving East-Asian countries and the United States. (October 2022) - Zhang, Dake; Siegler, Robert S
Abstract : To advance understanding of the gap in fraction learning between students in high-achieving East-Asian countries and the United States, we examined both intended curricula (i.e. standards) and implemented curricula (i.e. textbooks) in East Asia and the United States. Many similarities were present in both standards and textbooks. However, U.S. students began studying fractions earlier and studied them over more grades, and East-Asian instruction was more concen trated and included more mathematically challenging problems. Additionally, U.S. standards and textbooks tended to contextualize problems and emphasize the part–whole and measurement models of fractions, whereas East-Asian curricula tended to teach fraction concepts within the context of multiplicative reasoning and to teach fraction operations as an extension of whole-number operations. Educational implications of the findings about input are discussed. Abstract : Highlights: Compared intended curricula (i.e., standards) and implemented curricula (i.e., textbooks) in East Asia to those in the US. U.S. students began studying fractions earlier and studied them over more grades. East Asian instruction was more concentrated and included more mathematically challenging problems. U.S. textbooks tended to contextualize problems and emphasize the part-whole and measurement models of fractions. East Asian textbooks taught fractions within the context of multiplicative reasoning and as an extension of whole number operations.